Levels of vascular endothelial growth factor are elevated in the vitreous of patients with subretinal neovascularisation. Issue 4 (April 1996) - Wells, J A; Murthy, R; Chibber, R; Nunn, A; Molinatti, P A; Kohner, E M; Gregor, Z J
Abstract : BACKGROUND: Vascular endothelial growth factor (VEGF) has been shown to play a major role in intraocular neovascularisation in ischaemic retinal diseases. Subretinal neovascularisation is an important cause of central visual loss, but little is known about the role of this growth factor in its pathogenesis. The aim of this study was to investigate the possible role of VEGF in the development of subretinal neovascularisation. METHODS: Undiluted vitreous samples were obtained from patients undergoing vitrectomy for removal of non-age-related subfoveal neovascular membranes (SFNM). For comparison vitreous from patients undergoing vitrectomy for idiopathic full thickness macular holes (FTMH) and proliferative diabetic retinopathy (PDR) was used. Indirect enzyme linked immunosorbent assay (ELISA), with an antibody directed against the conserved N-terminal region of human VEGF165, was used to determine vitreous levels of VEGF. The growth factor was also localised in the vitreous of patients with SFNM by western blot analysis. RESULTS: The mean (SE) VEGF concentration in the vitreous of patients with SFNM was 27.78 (2.22) ng/ml (n = 8), FTMH was 16.62 (0.9) ng/ml (n = 18), and PDR was 37.77 (3.28) ng/ml (n = 16). The differences between the PDR group and SFNM group versus the FTMH group were both significant (p = 0.0001 and p = 0.0015) as analysed by the Wilcoxon rank sum test). CONCLUSIONS: Vitreous levels of VEGF are significantly elevated in eyes with non-age-related subretinal neovascularisation compared with eyes with FTMH but not as elevated as in PDR. This suggests that VEGF is involved in subretinal angiogenesis.